Myxomatous mitral valve disease in the miniature poodle: A retrospective study. (February 2019) - Meurs, K.M.; Adin, D.; O'Donnell, K.; Keene, B.W.; Atkins, C.E.; DeFrancesco, T.; Tou, S.
Highlights: Mxyomatous mitral valve degeneration (MMVD) in the miniature poodle was characterized. Medical records from 32 miniature poodles with MMVD diagnosed at a tertiary hospital were retrospectively evaluated. Mean age was 11 years. Eighteen dogs were classified as ACVIM Stage B1, 12 as B2, and two as C. There were no Stage D dogs. Mean vertebral heart scale (VHS) was 10.2 (±standard deviation of 0.9); 15 of the 28 dogs had a VHS <10.3. In the miniature poodle, MMVD appears to be a fairly late onset disease with a mild phenotype, at least in many cases. Abstract: Myxomatous mitral valve disease (MMVD) is the most common cardiovascular disease in the dog. The natural history of the disease is wide ranging and includes patients without clinical signs as well as those with significant clinical consequences from cardiac arrhythmias, pulmonary hypertension and/or congestive heart failure. The factors that determine which dogs remain asymptomatic and which develop clinical disease are not known. Disease characteristics could be breed or family related; some breeds of dogs, particularly the Cavalier King Charles spaniels, develop MMVD at an early age. The purpose of this study was to retrospectively characterize MMVD in the miniature poodle, a commonly affected breed in which MMVD has not been well characterized. Thirty-two miniature poodles met the inclusion criteria. Mean age was 11 ± three years. Clinical signs included exercise intolerance, syncope and coughing. Eighteen dogs were classified as ACVIM Stage B1, 12 as stage B2, and two as stage C. Mean vertebral heart scale (VHS) was 10.2 (±standard deviation of 0.9); 15 of 28 dogs had a VHS <10.3. One dog had radiographic evidence of congestive heart failure. Mean diastolic left ventricle dimension normalized to body weight was 1.6 (±0.4) and mean systolic was 0.8 (±0.3). Mitral valve prolapse was subjectively classified as mild or moderate in 19 dogs and severe in two. In the miniature poodles reported here, MMVD appears to be a fairly late onset disease and often is a mild phenotype.